Doppelgänger Architecture : The Dialectical Pair as a Representational System - Carruthers, Luz (Cuadernos de Proyectos Arquitectónicos, 2018)
AbstractThis paper proposes to examine the role of the doppelgänger as a representational system in architecture. In this field, the figure of the double shows particular nuances derived from its spatial and material condition. The architectural project must face the challenge to build a pair of elements working as a unit and the dialectical relationship established between them. The working hypothesis considers the doppelgänger as a reiterative character in architecture, with its own expressive charge derived from its ambivalent condition between duple and unit, and the kind of relationship existing among its elements geometrical, phenomenological, and structural. The doppelgänger is a character inherited from popular culture and introduced in the artistic production by means of the romanticism in literature. Multiple authors have used the double as an operational resource through different functions: split personality, consciousness or alter ego. In the artistic field, the doppelgänger is a representational system widely spread and studied for its value as a technique to question what is real, original and antagonistic. Nevertheless, in architecture there has not been an inquiry into its implementation in the project, neutralizing its conceptual background and waiving the possible consequences of its use. As a methodology, the theoretical implications underneath the architectural assemblage of the dialectic pair will be examined, as an operational mechanism and symbolic model, and selected architectural pieces will be reviewed to study different ways to build the dialectical pair. Through this analysis, it will be attempted to identify the predominant logic on which this representational system stands and to draw the possible consequences of its implementation in the architectural realm.